Examining the divergent effects of perceived inclusion of ethnic minorities on majority and minority groups’ inter-ethnic responses - Andriessen, Iris; Gündemir, Seval; Kappelhof, Joost W. S.; Homan, Astrid C. (Frontiers in Psychology, 2023)
Drawing from group conflict models, this study examines the paradoxical effects of a perceived inclusive environment for ethnic minorities. We argue and show that while such an environment may improve belonging and participation among minority groups, it may also instill a sense of threat among the majority group, resulting in negative intergroup sentiments and attitudes towards minorities. Conversely, perceptions of an inclusive environment may be associated with more positive intergroup attitudes and affect among minority groups. Findings from two waves of a nationally representative survey conducted in the Netherlands (ntotal=11,897) offer support for the proposed paradoxical relationship between the perceived inclusionary climate towards minorities and the attitudes of the majority and minority groups.The results indicate that when perceiving the national climate to be more inclusive towards minorities, the majority group tends to report higher levels of ethnocentrism, avoid direct inter-ethnic contact, and oppose ethnic diversity in general. Among minority groups, perception of an inclusive climate is negatively related to ethnocentrism and positively associated with inter-ethnic contact with the majority group. The results unexpectedly also show that the perception of an inclusionary climate is positively related to opposition to increased ethnic diversity among minority groups. We discuss the implications for intergroup relations in societies that seek to promote diversity and inclusion.